2017
DOI: 10.1007/s11999-016-5224-2
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Timing of General Health Adverse Events That Occur After Total Joint Arthroplasty?

Abstract: Background Despite extensive research regarding risk factors for adverse events after total joint arthroplasty (TJA), there are few publications describing the timing at which such adverse events occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 38 publications
6
44
0
Order By: Relevance
“…Our results are consistent with the findings of recent research from Johnson et al and BOHL et al [12,13]. Johnson et al [13] studied 1622 patients with PE after TJA based on the National Surgical Quality Improvement Program (NSQIP) database between 2011-2016, and indicated that the median day for PE following TJA was 3.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with the findings of recent research from Johnson et al and BOHL et al [12,13]. Johnson et al [13] studied 1622 patients with PE after TJA based on the National Surgical Quality Improvement Program (NSQIP) database between 2011-2016, and indicated that the median day for PE following TJA was 3.…”
Section: Discussionsupporting
confidence: 92%
“…Johnson et al [13] studied 1622 patients with PE after TJA based on the National Surgical Quality Improvement Program (NSQIP) database between 2011-2016, and indicated that the median day for PE following TJA was 3. BOHL et al [12] included 625 patients with PE after TJA from 2005 to 2013 based on the above database as well. The results showed that the median day of PE was 3 postoperatively (interquartile range: 2-7).…”
Section: Discussionmentioning
confidence: 99%
“…obtained similar results, with medians of 5 days and 4 days for pulmonary embolism, and 10.5 days and 12 days for DVT, respectively . This is also close to other observations made for orthopedic surgery: a median of 3 days for pulmonary embolism after lower‐limb arthroplasty, and 50% of thromboembolic events in the first 7 days after total shoulder arthroplasty .…”
Section: Discussionsupporting
confidence: 88%
“…To the best of our knowledge, no previous studies analyzed hospital readmissions or their economic impact in developing countries. Moreover, a 30-day interval is considered an overly short period to properly determine the consequences of a major surgical procedure [18,19]. With this as background, we performed a prospective analysis of unplanned readmissions within 90 days following spine surgery, regardless of the type or location of the procedure, in an orthopedic specialty unit.…”
Section: Introductionmentioning
confidence: 99%